Pengaruh perubahan telajakan dan apa dampak terhadap ruang terbuka hijau di Kelurahan Penatih, Denpasar Timur - Aryadiva, I Gusti Ngurah Aditya; Semarajaya, Cokorda Gede Alit; Astawa, I Nyoman Gede (Jurnal Arsitektur Lansekap; Vol.5, No.1, April 2019, 2019)
The effect of changes telajakan and what impact on green open space in Kelurahan Penatih, Denpasar Timur Telajakan is one of Bali's ancestral heritage which is usually used as a garden with various types of vegetation in it. However, currently telajakan has changed a lot. The purpose of this research is to know what factors caused the change of telajakan and what changes happened to green open space in the research location. Data collection methods used were observation, interview and literature study. The tools used in supporting research were office stationery, hand phone, measuring instrument, digital camera, interview list, and computer peripheral, Microsoft Word, Auto CAD. Based on the results of this study, it can be concluded that the form of the change of telajakan into a place of selling due to economic factors. The width of the telajakan changed 936 m² with a total area of 1028.5 m² overall. The change of telajakan in Kelurahan Penetih was 91.1%. The magnitude of changes that occurs can result in reducing green open space and affecting the micro climate in Penatih.